Proceedings of the ACM 2012 Conference on Computer Supported Cooperative Work 2012
DOI: 10.1145/2145204.2145290
|View full text |Cite
|
Sign up to set email alerts
|

Remix and play

Abstract: Players can change the rules of a multi-person game to experience a different gameplay mechanic, add thematic color, or fine-tune its balance. To better understand game variants, we use a grounded approach to analyze 62 variants for Texas Hold'em, a popular card game, and a follow-up case-study of 91 variants of Halo 2, a popular video game. We study their development and examine whether lessons from Texas Hold'em apply to a constrained system such as Halo 2. We discover video gamers' reliance on 'honor rules'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This study found the low-automation version required players to be more involved in the rule-interpretation process. A third is a study of invented custom games of Halo 2 (Cheung & Huang, 2012), an online multiplayer computer game. The study found that players develop ''honor rules'' to enforce new games that are socially sanctioned.…”
Section: ''Flexible'' Game Systems Designmentioning
confidence: 99%
“…This study found the low-automation version required players to be more involved in the rule-interpretation process. A third is a study of invented custom games of Halo 2 (Cheung & Huang, 2012), an online multiplayer computer game. The study found that players develop ''honor rules'' to enforce new games that are socially sanctioned.…”
Section: ''Flexible'' Game Systems Designmentioning
confidence: 99%